Enhancement of the Spin Pumping Effect by Magnon Confluence Process in YIG/Pt Bilayers. Issue 9 (29th April 2019) - Noack, Timo B.; Vasyuchka, Vitaliy I.; Bozhko, Dmytro A.; Heinz, Björn; Frey, Pascal; Slobodianiuk, Denys V.; Prokopenko, Oleksandr V.; Melkov, Gennadii A.; Kopietz, Peter; Hillebrands, Burkard; Serga, Alexander A.
Abstract : The experimental investigation of the spin pumping process by dipolar‐exchange magnons parametrically excited in in‐plane magnetized yttrium iron garnet/platinum bilayers is presented. The electric voltage generated in the platinum layer via the inverse spin Hall effect (ISHE) results from contributions of two opposite spin currents formed by the longitudinal spin Seebeck effect and by the spin pumping from parametric magnons. In the field‐dependent measurements of the spin pumping‐induced component of the ISHE‐voltage, a clearly visible sharp peak is detected at high pumping powers. It is found that the peak position is determined by the process of confluence of two parametrically excited magnons into one magnon possessing twice the frequency and the sum of the wavevectors of the initial magnons. It is demonstrated that under the action of a rather strong parametric pumping field this confluence process results in the increase of the total number of magnons in the magnetic sample, and thus leads to the enhancement of the spin pumping effect. Abstract : An enhancement of the spin pumping effect in parametrically driven YIG/Pt bilayers is registered in the presence of three‐magnon confluence of excited magnons. In spite of an additional damping, which is constituted by the confluence process for these magnons, the total number of parametric and confluenced magnons increases under strong parametric pumping leading to the observed enhancement.